Increasing the efficiency of heat and mass exchange in an improved rotary film evaporator for concentration of fruit-and-berry puree - Zahorulko, Andrii; Zagorulko, Aleksey; Yancheva, Maryna; Ponomarenko, Nataliia; Tesliuk, Hennadii; Silchenko, Ekaterina; Paska, Mariia; Dudnyk, Svetlana (Eastern-European Journal of Enterprise Technologies, 2020)
An improved model of a rotary film evaporator with a cutting blade having a reflective surface and equipped with an autonomous heating system which is fed by a power supply from Peltier elements. The reflective surface of the advanced cutting blade had an area of 0.06 m2 and was heated by a flexible film resistive electric heater of radiating type with a ~15...20 W power supply. This solution provides additional heating and mixing and helps to capture the cut-off layer of puree while reducing the useful surface of the working chamber by 7 %. Most evaporators have a low heat transfer coefficient reducing the energy content of the process and final quality of the product. The heat exchange efficiency can be increased by improving the design of the film-forming element of the rotary film evaporator. The use of the proposed cutting blade with a reflective surface enables an increase in the heat transfer coefficient by approximately 20 % compared to the basic rectangular blade design. When comparing the calculated data, it can be concluded that the main indicator of resource efficiency, namely specific energy consumption for heating a unit volume of product in the RFE amounts to 408 kJ/kg compared to 1,019 kJ/kg with the basic vacuum evaporator which means a 1.97 times consumption reduction. The duration of heat treatment in the RFE is 60 s compared to 1 h in the basic VE which shows a significant reduction of raw material exposure to high temperatures. The obtained data show the effectiveness of engineering and technological solutions. The engineering and technological component of any heat and mass exchange processes, in particular the concentration of fruit-and-berry raw materials, is the main component in the production of semi-finished food products of a high degree of readiness